Industrial structure and market conduct - Pickering, J. F. (London : Martin Robertson, 1974)
Deals with key issues affecting the performance of firms and industries, incorporating much empirical information, and discussion of government policies towards industry.
Includes bibliographical references and index.
lje 19/02/2018
Loans
Keywords: Industrial organization; Industrial policy; Marketing